PROSPECTS FOR THE DEVELOPMENT OF ELECTRONIC MONEY IN THE REPUBLIC OF UZBEKISTAN (Academicia Globe: Inderscience Research, 2022)
Payment methods for services and products are rapidly evolving in the world of e-commerce. Through constant innovation, payments are becoming more efficient and convenient for shoppers using online platforms. Merchants also benefit from improved processing navigation systems that help overcome differences in currencies, tax laws, and funds transfers.